Legally Binding of the World Trade Organization Dispute Settlement Body’s Decision - Yohanes, Triyana; Sulistiyono, Adi; Hawin, M. (Hasanuddin Law Review, 2017)
Dispute settlement system of the WTO DSB can be categorized as a judicial dispute settlement system. Decision (rulings and recommendations) in a dispute settlement made by the WTO DSB is binding and should be performed. In some cases, decisions made by the WTO DSB were not performed, and there is no sanction against the non-compliance with the decisions. The objective of this study is to analyze the legally binding character of the WTO DSB’s decision as a decision of a judicial organ. From the data analysis, it can be concluded that the WTO does not provide adequate sanctions against the non-compliance with the DSB’s decision. It leads to the interpretation of the DSB’s decision is international soft law norm which is not legally binding. Moreover, it can hamper the enforcement of the WTO Agreement and the achievement of the WTO’s goals. The WTO judicial system should be strengthened and improved by creating WTO independent court or tribunal, which has authority to make legally binding decision as international hard law.